Migrant mortality differences in the 2000s in Belgium: interaction with gender and the role of socioeconomic position - Katrien Vanthomme; Hadewijch Vandenheede (BMC, 2019)
Abstract Background Belgium has a long history of migration. As the migrant population is ageing, it is crucial thoroughly to document their health. Many studies that have assessed this, observed a migrant mortality advantage. This study will extend the knowledge by probing into the interaction between migrant mortality and gender, and to assess the role of socioeconomic position indicators in this paradox. Methods Individually linked data of the 2001 Belgian Census, the National Register and death certificates for 2001-2011 were used. Migrant origin was based on both own and parents' origin roots. We included native Belgians and migrants from the largest migrant groups aged 25 to 65 years. Absolute and relative mortality differences by migrant origin were calculated for the most common causes of death. Moreover, the Poisson models were adjusted for educational attainment, home ownership and employment status. Results We observed a migrant mortality advantage for most causes of death and migrant groups, which was strongest among men. Adjusting for socioeconomic position generally increased the migrant mortality advantage, however with large differences by gender, migrant origin, socioeconomic position indicator and causes of death. Conclusions Adjusting for socioeconomic position even accentuated the migrant mortality advantage although the impact varied by causes of death, migrant origin and gender. This highlights the importance of including multiple socioeconomic position indicators when studying mortality inequalities. Future studies should unravel morbidity patterns too since lower mortality not necessarily implies better health. The observed migrant mortality advantage suggests there is room for improvement. However, it is essential to organize preventative and curative healthcare that is equally accessible across social and cultural strata.